2019
DOI: 10.1292/jvms.19-0133
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of pigs with a classical swine fever virus isolated in Japan for the first time in 26 years

Abstract: Following an outbreak of classical swine fever (CSF) in Japan, 2018, CSFV JPN/1/2018 was isolated from an infected pig sample. In this study, we carried out a comparative experimental infection in pigs using this strain and the highly virulent ALD strain and compared outcomes, including clinical manifestation, virus shedding patterns and antibody responses. Although pigs inoculated orally or intramuscularly with JPN/1/2018 developed hyperthermia and had decreased leucocyte numbers, they survived for the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
53
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 17 publications
4
53
0
Order By: Relevance
“…Recently, CSF have been reported in Gifu Prefecture, affecting domestic pigs and wild boars since September 2019 in Japan [8,9]. The current circulating CSFV in Japan was identified moderate pathogenicity and most closely matched in nucleotide identity, with CSFVs recently isolated in China and Mongolia [8]. A space-time permutation analysis in Japan showed virus transmission spread (10.3 and 4.9 days/km) among wild boars in two significant clusters [9].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recently, CSF have been reported in Gifu Prefecture, affecting domestic pigs and wild boars since September 2019 in Japan [8,9]. The current circulating CSFV in Japan was identified moderate pathogenicity and most closely matched in nucleotide identity, with CSFVs recently isolated in China and Mongolia [8]. A space-time permutation analysis in Japan showed virus transmission spread (10.3 and 4.9 days/km) among wild boars in two significant clusters [9].…”
Section: Introductionmentioning
confidence: 91%
“…A high density of wild boars, particularly young wild boars, drives CSF outbreaks [7]. Recently, CSF have been reported in Gifu Prefecture, affecting domestic pigs and wild boars since September 2019 in Japan [8,9]. The current circulating CSFV in Japan was identified moderate pathogenicity and most closely matched in nucleotide identity, with CSFVs recently isolated in China and Mongolia [8].…”
Section: Introductionmentioning
confidence: 97%
“…In September 2018, the first CSF outbreak in Japan for 26 years was reported [15,16]. Despite countermeasures being taken, including the culling of infected herds and movement restrictions, the infection has continued to spread in 10 prefectures, resulting in 57 outbreaks and a total of 165,186 pigs culled as of 2 March 2020 [17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also shown that moderate virulence strains are widely distributed [13][14][15]. In this regard, the strain of CSFV that recently caused an epidemic in Japan after 26 years has been characterised to be of moderate virulence [16,17].…”
Section: Introductionmentioning
confidence: 99%